Citra Perempuan Soviet dalam Cerita Pendek Вера/Vera Karya Evgeniya Nekrasova - Elliane Adara Baelicia Panggabean; Thera Widyastuti (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research discusses the image of Russian women in the short story entitled Вера/Vera by Evgeniya Nekrasova. The aim of this research is to determine the image of Russian women in the Soviet era through analysis of the characters in the short story. This research uses descriptive analytical methods. Then it is complemented by an approach to intrinsic and extrinsic elements. The theories used are character-characterization and existentialist feminism. The author sees that the short story entitled Вера/Vera by Evgeniya Nekrasova presents a new view regarding how the younger generation of Russians view the image of Russian women in the Soviet era. Thus, this research shows the image of Soviet women through the female characters in the short story Вера/Vera, namely Vera and Tonya who are intelligent, hardworking, strong, adaptive, firm, disciplined, and caring in getting through the conflicts in their lives that occurred during the Soviet era.